The Effectiveness of Dart Game in Teaching Writing Descriptive Text - Maliqul Hafis; Wahyuni (PT. Media Edukasi Borneo, 2020)
The study aimed to investigate the effectiveness of the Dart game in teaching writing descriptive text. Pre-experimental research in the form of one group pre-test and post-test design was employed. The sample was selected through cluster random technique toward one of State Senior High School (SMAN) in west Borneo, Indonesia. Writing pre-test and post-test were conducted to gather the data. The data were, then, analyzed by using descriptive statistics. The result indicated that the Dart game was positively effective to teach the descriptive text. It is recommended that teachers should be aware that the use of Dart games does not necessarily guarantee better performance among EFL students when it comes to writing descriptive text. Therefore, they should create a language learning environment in which they encourage students to write in the target language to improve the quality of their writing.